Therapeutic Mastoidectomy Does Not Increase Postoperative Complications in the Management of the Chronic Ear. Issue 1 (January 2018) - Shew, Matthew A.; Muelleman, Thomas; Villwock, Mark; Muelleman, Robert J.; Sykes, Kevin; Staecker, Hinrich; Lin, James L.
Abstract : Objective: Tympanoplasty with or without concurrent therapeutic mastoidectomy is a controversial topic in the management of chronic ear disease. We sought to describe whether there is a significant difference in postoperative complications. Study Design: Retrospective cohort study. Setting: American College of Surgeons National Surgical Quality Improvement Program public files. Patients: Current procedural terminology codes were used to identify patients with chronic ear disease undergoing tympanoplasty ± concurrent mastoidectomy in the 2011 to 14 American College of Surgeons National Surgical Quality Improvement Program files. Intervention: Therapeutic. Main Outcome Measures: Variables were compared with χ 2, Fischer's exact, and Mann–Whitney U tests, as appropriate to analyze postoperative complications between tympanoplasty with or without concurrent mastoidectomy. To account for confounding factors, presence of a complication was analyzed in binary logistic regression. Analysis considered sex, hypertension, obesity, advanced age, diabetes, smoking status, American Society of Anesthesiologists Physical status, procedure. Results: There were 4, 087 patients identified meeting criteria (tympanoplasty = 2, 798, tympanomastoidectomy = 1, 289). There was no statistical difference in postoperative complications (tympanoplasty n = 49 [1. 8%], tympanomastoidectomy n = 33 [2. 6%]; p  = 0. 087) or return to the operating room (tympanoplasty = 4 [0. 1%], tympanomastoidectomy = 6 [0. 5%]; p  = 0. 082). Binary logistic regression demonstrated smoking as a predictor of a postoperative complication (OR: 1. 758, 95% CI: 1. 084–2. 851; p  = 0. 022), while concurrent mastoidectomy did not significantly increase the risk of complication (OR: 1. 440, 95% CI: 0. 915–2. 268; p  = 0. 115). There was a significant difference in mean operative time between tympanoplasty and tympanomastoidectomy: 85.7 versus 154.23 min, p  < 0. 001. Conclusion: In the management of chronic ear disease, tympanoplasty with concurrent mastoidectomy increases time under anesthesia, but it is not associated with any increased postoperative complications compared with tympanoplasty alone.